PERAN BADAN NASIONAL PENANGGULANGAN BENCANA DALAM PENANGANAN PANDEMI COVID-19 DI KABUPATEN GARUT - Desvita Dianti Wiratami; Muhammad Nasrul; A. Inayah Ainun Fajriyah (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2021)
The COVID-19 pandemic that has emerge and attacked Indonesia since the beginning of 2020 has intensified the demands for the role of the government to formulate a specific kind of policies that can address and accommodate social, economic, and political problems that arise as a consequence of this non-natural disaster. In an effort to cope with this disaster, the government has given a mandate to BNPB to take the strategic steps needed so that this pandemic is quickly finished, not least in Garut Regency, West Java. By implementing a qualitative descriptive research method, this study aims to methodologically and comprehensively analyze the role of BNPB in handling the COVID-19 pandemic in Garut Regency. The role of BNPB is very crucial considering the magnitude of the mandate carried out in an effort to mitigate the risk of the COVID-19 Pandemic disaster in Garut Regency, West Java. Keywords: COVID-19 Pandemic; BNPB’s Role; Disaster Management; Comprehensive Studies.